Islam and the West : Problematizing a Discourse of Dualism - Lean, Nathan Chapman (East Carolina University, 2010)
"Islam and the West," a dualistic phrase that gained sudden ascendancy following the events of September 11, 2001, is used variously to refer to the mutual relationship between Muslims and those living in a sometimes ill-defined region called "the West." The binary phrase in question serves to reify what are depicted as incommensurate and incompatible opposites in terms of politics, culture, religion, and otherwise. This thesis argues that the perceived division between Islam and "the West" arises within a discourse that presumes, configures, and reinforces a relationship of conflict between the two. Coming from different viewpoints, the individuals examined in this thesis end up deploying similar linguistic maneuvers that advance their own ideological beliefs, reinforce their self-identities, and represent their respective values as universal. As a result, each group views the other as threatening and necessarily oppositional. An analysis of key terms and phrases used by influential scholars, political and religious leaders, and the general public within "Western" and Muslim-majority societies will reveal the constructed nature of the division between Islam and "the West." Additionally, this thesis will examine the ways in which other discursive practices such as selective representation, reification, and the deployment of charged stereotypes influence policy makers who seek to establish global positions of power. By problematizing the language that both sides of this perceived dualism use to represent themselves and the other, it will be demonstrated that the perceived conflicting relationship between Islam and "the West" results, in part, from the linguistic practices that each side deploys.
Keywords: Religion, General; Islamic countries--Relations--Western countries; Western countries--Relations--Islamic countries; Sociolinguistics--Cross-cultural studies; Language and culture; Ethnic conflict; Islamic civilization; Civilization, Western; Islamophobia; Intercultural communication; East and West